Consumer Protection in the Circulation of Illegal Cosmetics in Indonesia: An Analysis of Business Ethics, Legal Regulations, and Corporate Governance - Wijaya, Sony; Satory, Agus (Cerdika: Jurnal Ilmiah Indonesia, 2026)
The rise of illegal cosmetic products in Indonesia has become a significant concern for consumer protection, public health, and corporate accountability, particularly amid the rapid growth of digital marketplaces. Despite the existence of regulatory frameworks governing cosmetic safety, the circulation of unregistered and hazardous products continues to increase, driven by weak regulatory enforcement, inadequate oversight of online commerce, and misleading practices by sellers. This research used normative legal method and qualitative approach. The data is secondary data and taken from laws and regulations, regulations, official reports, journal articles, and credible online sources. The findings indicate that the current regulatory regime exhibits major deficiencies, including fragmented legal norms, limited inspection capacity, and the absence of clear liability standards for marketplace operators. These conditions have enabled illegal cosmetics many containing banned or harmful substances to enter the supply chain and reach consumers without effective preventive controls. The research further reveals that ethical business principles and corporate governance mechanisms are often undermined by profit-driven motives, resulting in “false compliance” by some platforms that outwardly adopt safety policies without substantively implementing them. The study argues that reinforcing consumer protection requires harmonizing relevant regulations, strengthening oversight of digital commerce, and imposing clearer obligations on marketplace operators, potentially through the adoption of stricter liability frameworks. Future research may explore technological solutions for product authentication, cross-border regulatory cooperation, and comparative legal models that address platform responsibility in the digital ecosystem.